The Influence of Discipline on Employee Performance which is Strengthened through Work Motivation in the General Section of the Directorate General of Infrastructure Financing of the Ministry of PUPR Using the Structural Equation Modeling (SEM) Method - Marendra, I Gede; Aryata, I Made (Jurnal Manajemen dan Organisasi, 2024)
The Directorate General of Public Works and Housing Infrastructure Financing has the task of carrying out the formulation and implementation of policies in the field of financing public works and housing infrastructure in accordance with the provisions of statutory regulations. Quality human resources can support good employee performance, so it is important for organizations to be able to identify the factors that influence employee performance so that the organization can take appropriate steps to improve employee performance. Human Resources within the Directorate have an important role in the success of financing needed for infrastructure development. The aim of this research is to determine the direct and indirect influence of the Work Discipline variable on employee performance with Motivation as a moderating variable. This type of research is quantitative research with a sample size of 55 people. The method used in this research is Structural Equation Modeling (SEM), which is a combination of two analytical methods, namely factor analysis and path analysis into one comprehensive statistical method. From the results of the research carried out, it is known that: 1) Work Discipline influences employee performance, this is proven by the estimated value of 0.988; 2) Motivation has no effect on employee performance, this is proven by the negative estimate value of -0.503 and 3) Motivation as a moderating variable strengthens the influence of work discipline on employee performance with a p-value of 0.000.